2019
DOI: 10.13005/bpj/1766
|View full text |Cite
|
Sign up to set email alerts
|

Bone Health in Relation to Vitamin-D Status and Serum Adipokines in Obese Egyptian Children

Abstract: Childhood obesity has been linked to an increase in fracture risk, so the impact of obesity on bone metabolism is becoming a focus of attention to identify factors that may affect bone health in obese children. Therefore, this study aimed to examine the association between serum 25-Hydroxy vitamin D [25(OH) D], adipokines and bone status in obese children. This case control study was executed in the Child Health Clinic in Medical and Scientific Centre of Excellence, National Research Centre (NRC), 100 obese an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…These findings are compatible with [13] reported that orange peel waste significantly inhibited growth of canary grass and cheese weeds in pots experiment. [41] reported that mango leaves waste had allelopathic effects and significantly suppressed the shoot and root biomass of Parthenium hysterophorus L. in both petri dish and pot trails.…”
Section: Weed Density and Weed Growth Inhibition In Greenhouse Experi...supporting
confidence: 93%
See 1 more Smart Citation
“…These findings are compatible with [13] reported that orange peel waste significantly inhibited growth of canary grass and cheese weeds in pots experiment. [41] reported that mango leaves waste had allelopathic effects and significantly suppressed the shoot and root biomass of Parthenium hysterophorus L. in both petri dish and pot trails.…”
Section: Weed Density and Weed Growth Inhibition In Greenhouse Experi...supporting
confidence: 93%
“…The gradual accumulation or incorrect disposal of these wastes may cause environmental problems [10]. Recent studies reported that some agro-industrial wastes, such as orange peel, olive oil mill wastes and mango leaves, have allelopathic effect and could be utilized in weed control as natural products [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D is a steroid hormone that has a great role in calcium and phosphorus homeostasis, bone metabolism and bone development [5], [6]. Recently the role of vitamin D on glucose homeostasis, cardiovascular diseases, immune system and cancer has been reported [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some have also found a significant association between obesity and vitamin D deficiency ultimately leading to fractures. Increased adipose tissue leads to inadequate mineralisation leading to bone fractures 23 …”
Section: Discussionmentioning
confidence: 99%